Prevalence and antibiotic resistance of Staphylococcus aureus associated with a college-aged cohort: life-style factors that contribute to nasal carriage - Congdon, Sean T.; Guaglione, John A.; Ricketts, Omario M. A.; Murphy, Kyle V.; Anderson, Megan G.; Trowbridge, Darby A.; Al-Abduladheem, Yousuf; Phillips, Annabelle M.; Beausoleil, Allison M.; Stanley, Alexus J.; Becker, Timothy J.; Silver, Adam C. (Frontiers in Cellular and Infection Microbiology, 2023)
Staphylococcus aureus is an opportunistic human pathogen that can frequently be found at various body locations, such as the upper respiratory tract, nostrils, skin, and perineum. S. aureus is responsible for causing a variety of conditions, which range from minor skin infections and food poisoning to life-threatening sepsis and endocarditis. Furthermore, S. aureus has developed resistance to numerous antimicrobial agents, which has made treatment of S. aureus infections difficult. In the present study, we examined lifestyle factors that could increase the likelihood of S. aureus carriage, the overall prevalence of S. aureus, as well as assessed the antibiotic resistance profiles of the S. aureus isolates among a population of college students. Five hundred nasal samples were collected and analyzed via selective growth media, coagulase and protein A testing, as well as polymerase chain reaction and DNA sequencing. One hundred four out of the 500 samples collected (21%) were identified as containing S. aureus. The S. aureus isolates were resistant to penicillin (74%), azithromycin (34%), cefoxitin (5%), ciprofloxacin (5%), tetracycline (4%), and trimethoprim (1%), but sensitive to gentamicin and rifampin. Lastly, we identified several lifestyle factors (i.e., pet exposure, time spent at the university recreational facility, musical instrument usage, and tobacco usage) positively correlated with S. aureus nasal colonization.